MORPHOLOGICAL CHANGES IN THE TESTES FOLLOWING DOMESTIC GAS POISONING AGAINST THE BACKGROUND OF CHRONIC ALCOHOLISM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This scientific article provides a comprehensive evaluation of the morphological transformations occurring within testicular tissues under the combined pathological influence of chronic alcoholism and acute household gas poisoning. The simultaneous exposure to chronic ethanol toxicity and acute carbon monoxide or hydrocarbon inhalation induces profound hypoxic conditions, severe oxidative stress, and structural disruptions in the male reproductive system. Histological examinations reveal extensive degradation of the seminiferous tubules, a significant reduction in spermatogenic epithelial cells, cellular vacuolation, and interstitial edema. Furthermore, the Leydig cells exhibit distinct dystrophic alterations, which directly correlates with a decline in endocrine function and impaired spermatogenesis. The findings underscore the synergistic detrimental effects of these two toxic agents, highlighting a accelerated pathway toward male infertility and gonadal dysfunction.